Transforming health care leadership : a systems guide to improve patient care, decrease costs, and improve population health - Maccoby, Michael, 1933- (San Francisco : Jossey-Bass, 2013)
"Health care organizations are challenged to improve care at the bedside for patients, learn from individual patients to improve population health, and reduce per capita costs. To achieve these aims, leaders are needed in all parts of the organization need positive solutions. Transforming Health Care Leadership provides healthcare leaders with the knowledge and tools to master the unprecedented level of change that health care organizations and their leaders now face. It also challenges management myths that served in bureaucracies but mislead in learning organizations"--Provided by publisher.
Introduction : from management myths to strategic intelligence -- Why and how health care organizations need to change -- Leading health care change -- Developing a leadership philosophy -- Leading with strategic intelligence and profound knowledge -- Changing health care systems with systems thinking -- Statistical thinking for health care leaders -- Understanding the psychology of collaborators -- A health care leader's role in building knowledge -- Three case studies : mastering change -- Leading change : first steps in employing strategic intelligence to get results.
Includes bibliographical references and index.
Keywords: Leadership -- United States; Delivery of Health Care -- organization & administration -- United States; Organizational Innovation -- United States